From Benign Origins to Final Moments: Right Ventricular Outflow Tract Premature Ventricular Complexes Culminating in Asystole on Holter Monitoring - Raharjo, Sunu Budhi; Raj, Sai Vhimal; Pritazahra, Armalya; Hanafy, Dicky Armein; Hermanto, Dony Yugo; Yuniadi, Yoga (Jurnal Kardiologi Indonesia, 2025)
Background: Premature Ventricular Complexes (PVCs) are a common cardiac arrhythmia typically of benign nature. Their origin, the right ventricular outflow tract (RVOT), is often a point of interest due to its implications in treatment strategies. While the vast majority of PVC RVOT cases remain uneventful, there are isolated incidents that challenge this common perception. Continuous monitoring methods, such as the Holter monitor, have provided invaluable insights into the real-world dynamics of arrhythmias, capturing rare events that can be of paramount clinical significance. Case Illustration: A 60-year-old female, presented to Harapan Kita Hospital Jakarta in May with palpitations. Over several visits, physical examinations consistently indicated a heart within normal parameters, absent of murmurs or gallop. Successive ECGs revealed persistent PVCs of RVOT origin. Despite medical intervention, her arrhythmic pattern persisted. By September, her symptoms had diversified, including occasional chest pain, nausea, and dyspnea. An ECG, yet again, confirmed PVCs with RVOT origin. During a Holter monitoring session on September, a distressing sequence of events was captured. The monitor initially registered a non-sustained Ventricular Tachycardia (VT). which escalated to sustained VT, ventricular fibrillation, and culminating in asystole, marking the patient's final moments. Conclusions: The pathophysiological journey from benign PVCs of RVOT origin to a fatal arrhythmic event underscores the unpredictability and inherent dangers of cardiac arrhythmias. This case is a reminder of the critical importance of persistent monitoring, timely interventions, and the nuanced understanding of conditions conventionally deemed 'benign'.